Perubahan Strategis di Perusahaan Fujifilm: Analisis Strategi Manajemen Perubahan Melalui Kotter's 8 Step Change Model untuk Meningkatkan Kinerja dan Inovasi - Nadia Jasmine; Guntur Haludin; Marcelina Putri Widayanto; Zahra Asyifa; Shanata Putri Martiza; Dewi Swangsa (CV. ULIL ALBAB CORP, 2025)
Fujifilm, which was founded in 1934, faced major challenges due to a significant decline in its photographic film business along with the development of digital technology. From contributing 60% of sales in 2000, this sector shrank to less than 10% in 2010. To survive and develop in the digital era, Fujifilm succeeded in carrying out a strategic transformation by shifting its business focus from photographic film to the pharmaceutical, cosmetics and digital technology sectors, and create new innovations. This research aims to analyze Fujifilm's transformation efforts using Kotter's 8 Step Change Model as a framework. The research method used is qualitative literature study using several sources in the form of e-books, industry articles and related publications. The research results show that Fujifilm's success in change management lies in their ability to adapt and innovate continuously, as well as building a corporate culture that encourages openness and transparency.